Rancang Bangun Aplikasi Penilaian Kinerja Pegawai Pada Dinas Komunikasi Dan Informatika Provinsi Jawa Timur - Haditio, A.R. Bagas Danang; Sulistiowati, Sulistiowati; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Communications and Information Agency of East Java Province Control is an agency that was founded in 2008. It has 142 employees of which consists of the Secretariat, Network Communications, POSTEL, Infrastructure Management, and Information Dissemination, and IT development. The problem that occurs today is the loss of data, because there are still done manually (Ms.Excel), Making recap the results of employee performance evaluation requires a long time, often a calculation error in the assessment of performance, Requires a large space for storing files SKP, Reports can not be seen directly because the Head of Department should contact the secretariat to find out recapitulation of the report so as to allow for error and slow in the delivery of employee performance evaluation information. Based on the above problems, it is necessary application performance assessment based on BKN Chief Regulation Number 1 Year 2013 is an integrated inter-sections in the Communications and Information Agency of East Java province, so that with the employee performance evaluation that is integrated, agency heads may memonitor.Setelah tested the Employee JFU, application performance assessments, can help SKP assessment process, work behavior and work performance (Total ratings). And applications can generate recaps employee data and generate recommendations JFU.